Nazwy wiatru w języku mieszkańców wielkopolskich wsi na tle kultury regionu .......... 273 - Kobus, Justyna (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
NAMES FOR WIND IN THE LANGUAGE OF THE INHABITANTS OF GREATER POLISH VILLAGES IN THE CONTEXT OF THE REGION’S CULTURE The article discusses the names for various types of wind, as recorded in historical and contemporary dialectological studies in Greater Poland. The author adduces examples from both scientific sources and amateur dialectal dictionaries. She divides the scientific sources chronologically: Adam Tomaszewski’s index cards (1930s), maps and comments from the Atlas języka i kultury ludowej Wielkopolski (‘Atlas of the language and folk culture of Greater Poland’; 1970s and 1980s), and contemporary materials obtained from field research conducted after 2000. The main content of the article consists of three parts: general names and names for weak winds, names for strong winds, names for whirling winds. A dialectological characterization of the mentioned lexical groups is supplemented with ethnographic information from the cited sources.